Apoptosis-dependent Externalization and Involvement in Apoptotic Cell Clearance of DmCaBP1, an Endoplasmic Reticulum Protein of Drosophila - Okada, Ryo (American Society for Biochemistry and Molecular Biology, 2012)
To elucidate the actions of Draper, a receptor responsible for the phagocytic clearance of apoptotic cells in Drosophila, we isolated proteins that bind to the extracellular region of Draper using affinity chromatography. One of those proteins has been identified to be an uncharacterized protein called Drosophila melanogaster calcium-binding protein 1 (DmCaBP1). This protein containing the thioredoxin-like domain resided in the endoplasmic reticulum and seemed to be expressed ubiquitously throughout the development of Drosophila. DmCaBP1 was externalized without truncation after the induction of apoptosis somewhat prior to chromatin condensation and DNA cleavage in a manner dependent on the activity of caspases. A recombinant DmCaBP1 protein bound to both apoptotic cells and a hemocyte-derived cell line expressing Draper. Forced expression of DmCaBP1 at the cell surface made non-apoptotic cells susceptible to phagocytosis. Flies deficient in DmCaBP1 expression developed normally and showed Draper-mediated pruning of larval axons, but a defect in the phagocytosis of apoptotic cells in embryos was observed. Loss of Pretaporter, a previously identified ligand for Draper, did not cause a further decrease in the level of phagocytosis in DmCaBP1-lacking embryos. These results collectively suggest that the endoplasmic reticulum protein DmCaBP1 is externalized upon the induction of apoptosis and serves as a tethering molecule to connect apoptotic cells and phagocytes for effective phagocytosis to occur.